Spirituality and Resiliency among Natural Disaster Adult Survivors - Alcantara, Rogen Ferdinand E. (Silliman Journal, 2022)
This study aimed to determine the relationship between spirituality and resiliency among natural disaster adult survivors covering selected communities in two provinces using a survey method where a continuing calamity response program was enforced in 2012 and 2013. The results revealed that most of the respondents have experienced high spiritual struggles and may have coped with trauma through negative coping. On the other hand, most of the respondents regarded their resiliency level as neutral, indicating ambivalence about their ability to cope and bounce back. The results also pointed out that there were no significant relationships between spirituality and resiliency among survivors. Spirituality is a highly internal and personal process regardless of one’s physical condition and social needs, and it may or may not be directly related to resiliency. Nevertheless, the two disasters propelled the survivors to strive to make sense or continuously search for the meaning of their disaster experiences. With this, there is a need for balanced and holistic intervention and recovery programs for survivors to obtain a sense of optimal well-being, spiritual empowerment, and positive resiliency.